2014
DOI: 10.1111/aogs.12429
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum weight retention and breastfeeding among obese women from the randomized controlled Lifestyle in Pregnancy (LiP) trial

Abstract: We could not detect sustained weight control at 6 months postpartum despite a lower gestational weight gain for obese women during pregnancy who received a lifestyle intervention rather than standard care. Women who adhered to gestational weight gain recommendations had significantly lower postpartum weight retention. Breastfeeding for 6 months was negatively associated with postpartum weight retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 27 publications
6
93
1
3
Order By: Relevance
“…44 45 55 56 61–63 70–74 Three RCTs (intervention group, n=268; control group, n=261) could not be included in the meta-analysis (see online supplementary table 1). In the first, Vinter et al 76 reported similar maternal weight at 6 weeks postpartum in women who were randomised to a prenatal exercise + diet intervention (95 kg, 87.3–106.6 kg) and in those who were randomised to a control group (94.4 kg, 87–107.3 kg, P=0.878). The proportion of women meeting a postpartum weight loss goal of >0 kg and >5 kg was also similar in both groups 76.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…44 45 55 56 61–63 70–74 Three RCTs (intervention group, n=268; control group, n=261) could not be included in the meta-analysis (see online supplementary table 1). In the first, Vinter et al 76 reported similar maternal weight at 6 weeks postpartum in women who were randomised to a prenatal exercise + diet intervention (95 kg, 87.3–106.6 kg) and in those who were randomised to a control group (94.4 kg, 87–107.3 kg, P=0.878). The proportion of women meeting a postpartum weight loss goal of >0 kg and >5 kg was also similar in both groups 76.…”
Section: Resultsmentioning
confidence: 97%
“…In the first, Vinter et al 76 reported similar maternal weight at 6 weeks postpartum in women who were randomised to a prenatal exercise + diet intervention (95 kg, 87.3–106.6 kg) and in those who were randomised to a control group (94.4 kg, 87–107.3 kg, P=0.878). The proportion of women meeting a postpartum weight loss goal of >0 kg and >5 kg was also similar in both groups 76. Second, Ferrara et al 59 reported no effect of a prenatal exercise + co-intervention (diet and behavioural intervention) on the odds of meeting postpartum weight loss goals (goal based on pre-pregnancy BMI) at 6 weeks and 7 months postpartum.…”
Section: Resultsmentioning
confidence: 97%
“…Lactation is also associated with many positive long-term health outcomes, such as decreased risks of obesity and diabetes, and increased performance in intelligence tests during childhood and adolescence [1,3]. For mothers, the advantages of breastfeeding include reduced postpartum bleeding, faster return to pre-pregnancy weight, a lower risk of breast and ovarian cancer, as well as decreased risks of hip fractures and osteoporosis in later life [1,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Our data will provide evidence as to whether an intervention delivered only during pregnancy has a long lasting effect on postpartum weight retention once the intervention stops at delivery (e-intervention group 1) or whether there is an additive effect of a postpartum component to a pregnancy intervention by adapting the strategies to their new life stage. Previous studies have examined pregnancy intervention effects on weight measures at 2 months[41,42], 6[43], and 12 months[44] postpartum, and two others with a 12 month follow-up are underway,[45,46] but very few have tested interventions for both the pregnancy and postpartum periods. Huang TT, et al[17] tested a lifestyle intervention using a three-arm design until 6 months postpartum with positive results, and Rauh et al[47] have an ongoing cluster randomized pregnancy and postpartum intervention implemented until 6–8 weeks.…”
Section: Discussionmentioning
confidence: 99%